Late Neolithic and Bronze Age Settlements at Hemmed Church and Hemmed Plantation, East Jutland - Axel, Niels (Journal of Danish Archaeology, 1991)
Late Neolithic and Bronze Age Settlements at Hemmed Church and Hemmed Plantation, East Jutland